Green's functions for infinite and semi-infinite isotropic laminated plates - Wang, Xu (2016)
The Green's functions for an infinite and a semi-infinite Kirchhoff isotropic laminated plate subjected to concentrated forces, concentrated moments, discontinuous displacements and slopes are obtained. The explicit expressions of the three 4×4 real matrices H, L and S for an isotropic laminated plate are derived by using the complex variable formulation recently developed by the authors. Once the Green's functions for an infinite plate are known, those for a semi-infinite plate can be conveniently obtained by using analytical continuation. The image forces on a point dislocation with discontinuous in-plane displacements and slopes due to its interaction with a rigidly clamped edge and a free edge are presented by using the obtained explicit expressions of H and L. Finally, the surface Green's functions of concentrated forces and moments are obtained as a limiting case of the Green's functions for a semi-infinite plate with a free edge. Some interesting features of the surface Green's functions are observed.